A magyarországi kis - és középvállalkozások finanszírozása a 2008-as gazdasági válság óta - Juhász Ilona (2020)
A company’s decision about financing is key. Managing the right funding policy requires a great deal of expertise, as several principles need to be followed in order to achieve balanced funding. Access is determined on the one hand by reasons of company specificities and on the other hand by the external financing medium. Unfortunately, small and medium-sized companies often lack the right manager and financial manager who would be professionally competent in the subject. But this is not only an important issue for companies in terms of their financing future but also in terms of the economy, as they also contribute to the development of a gross domestic product. Small and medium-sized enterprises are major employers in each nation. Within the business sector, attitudes are different towards small and medium-sized enterprises. They differ from large companies in many respects: they are more disadvantaged by their size. Special measures are being taken by the European Union and national governments for the benefit of small and medium-sized enterprises. Credit institutions also offer them targeted product packages. In my dissertation, I describe the motives behind the special treatment. The focus on SMEs is also reflected in the fact that the EU has developed a separate indicator for their access to finance, which is constantly measured. During the period 2008-2019, we experienced a recession and recovery in our economy. We have witnessed various measures by banks and the state. Companies were (also) in a difficult situation, so in my dissertation, I examine their reaction to the crisis. My research relies on both quantitative and qualitative sources. I deal with financing theories first. My study also deals with an analysis of the financing attitudes of companies over the past 11 years in the light of changes in the external environment. The aim of this dissertation is to present a wide range of corporate financing opportunities, within which external sources are focused. I point out which of these are the most used by Hungarian SMEs, and I research the reasons behind them. Unfortunately, they only use a few major formats, although they would benefit from changing this. I am trying to critique each type of funding. Hungarian SMEs are special in several respects, 60% of them are family businesses and most of them operate in the service industry. To what extent do these features hinder their funding? With the help of the available statistical data and other surveys, I explore the correlations characteristic of the financing environment, with an emphasis on lending conditions. Lending has a long history and has long been mentioned as a basis for corporate and thus economic growth. The diversity of my work is shown by the fact that I describe the phenomena from the perspective of different participants. I present how the state can influence the financing environment and what measures it has taken in order to do so, I characterize our domestic credit market, I examine the statements and perceptions made by the banks and the companies separately.